CHARACTER DEVELOPMENT OF ELEMENTARY SCHOOL STUDENTS THROUGH VALUES EDUCATION: A LITERATURE REVIEW - Anantama, Raka (CV. Fahr Publishing, 2024)
This study aims to analyze and synthesize recent literature on character development in elementary school students through values education. Using a qualitative library research method, the study reviewed 22 peer-reviewed articles published between 2020 and 2025, selected through thematic relevance, educational context, and methodological clarity. Data were collected from international educational databases and analyzed through thematic coding to identify recurring strategies, challenges, and theoretical foundations. The findings reveal that values education is most effective when integrated holistically into school culture, classroom pedagogy, and teacher modeling. Common implementation strategies include thematic learning, project-based models, and character reinforcement through extracurricular activities. However, consistent barriers persist, such as lack of teacher training, insufficient character assessment tools, and external influences from digital media and home environments. The novelty of this research lies in its emphasis on the digital–pedagogical–cultural integration of values education in elementary settings, while also proposing a conceptual framework for ecosystemic character development. The study also highlights the limited research addressing early-grade learners (Grades 1–3) and the potential of participatory character-building approaches. In conclusion, the review confirms the importance of values education in shaping student character but underscores the need for systemic alignment, contextual adaptation, and long-term monitoring to ensure its effectiveness in modern school settings. These insights are expected to inform educational stakeholders in designing sustainable, culturally-responsive, and digitally literate character education programs for primary students.